Some thoughts on language of instruction at the University of the Philippines Diliman - Gaerlan, Barbara (Diliman, Quezon City UP-Education Research Program Center for Integrative and Development Studies, 1995)
"Gaerlan discusses some issues regarding the language of instruction at UP Diliman. She states that despite the passage of a language policy in 1989 under President Abueva, which declared Filipino as the medium of instruction for undergraduate classes within a reasonable time frame, English still continues to dominate majority of the classes at UP.
Moreover, within individual classes there exists extensive division of language use by area of discourse (i.e., oral or written). Many classes which are described as being conducted in English in fact permit Filipino to be used extensively for class discussion, whereas many classes identified as being conducted in Filipino use some (or frequently all) English reading materials. Although the faculty generally give their students a choice of writing their papers in English or Filipino, the students overwhelmingly prefer to write in English.
Though very preliminary, this paper provides important observations which may be useful to future studies on the language of instruction situation in UP and what must and can be done about it."
Work in progress. Please do not cite without permission.
Keywords: Language and languages -- Education -- Philippines